Comparison of red blood cell survival in sheep determined using red blood cells labeled with either biotin at multiple densities or [(14)C]cyanate: validation of a model to study human physiology and disease - Mock, Donald M. (2012)
BACKGROUND: Measurement of red blood cell (RBC) survival (RCS) is important for investigating pathophysiology and treatment of anemia. Our objective was to validate the multidensity biotin method for RCS determination in sheep, a commonly used model of RBC physiology. [(14)C]Cyanate served as the reference method for long-term RCS because the (51)Cr method (the reference method for humans) is not reliable in sheep. STUDY DESIGN AND METHODS: Aliquots of autologous RBCs from eight adult sheep were labeled with [(14)C]cyanate and four separate densities of biotin (BioRBCs) and reinfused. Short-term RCS was assessed by posttransfusion recovery at 24 hours (PTR(24)); long-term RCS was assessed by the time to 50% survival (T(50)) and mean potential life span (MPL). RESULTS: Values for PTR(24) of the four BioRBC densities were not different. Values for RCS as reflected by T(50) and MPL were nearly identical for [(14)C]cyanate and the two intermediate-density BioRBC populations. In contrast, the lowest-density BioRBC population survived slightly longer (p < 0.01), but with a difference of no clinical significance. The highest-density BioRBC population importantly shortened RCS (p < 0.01 compared to the two intermediate densities). CONCLUSION: This study provides evidence that BioRBCs labeled at four biotin densities can be used to independently and simultaneously measure short-term RCS and that BioRBCs labeled at the three lowest biotin densities can be used to accurately and simultaneously measure long-term RCS. Because the sheep RBC model is comparable to humans, this nonradioactive method has promise for use in RBC kinetic studies in neonates and pregnant women.